GERMAN EPISTOLARY HERITAGE OF IVAN FRANKO AND ITS DOMINANT FEATURES - V.V. Tkachivsky (Vasyl Stefanyk Precarpathian National University, 2015)
The epistolary heritage of Ivan Franko contains over six thousand letters. German epistolary correspondence addressed to Vienna, Berlin, Budapest, Heidelberg, Freiburg, Stanislav, Chernivtsi. The author of the article analyzes also the response letters sent to I. Franko. His first letters in German were addressed to Olha Roshkevych. They were written under the strong impression that the epistolary novel "The Sorrows of Young Werther" by J.W. von Goethe had had on I. Franko. The Ukrainian writer's correspondence with H. Kanner and I. Singer the editors of the weekly newspaper "Zeit" is an evidence of their close cooperation. I. Franko had close professional ties with V. Adler one of the founders and leaders of the Austrian social-democratic party, the editor of Vienna newspaper "Arbeiterzeitung", as well as with V. Adler's wife Emma. I. Franko's correspondence with a prominent Slavic scholar V. Yagic didn't contain only private matters discussions. The third part of it is totally scientific which actually makes it valuable for researchers. I. Franko's epistolary works reflect his artistic writer's style neither in form nor in content. His letters are characterized by the depth of his thought, consistency of his statements, clearness of the sentence constructions, tendency to critical assessments of phenomena and scientific findings.